Unveiling the immunomodulatory properties of starch microparticles on alveolar macrophages - Alejandra Barrera-Rosales; Dulce Mata-Espinosa; Vanessa Villegas-Ruiz; Mayra Silva-Miranda; Edgar Zenteno; Sergio Sánchez; Rogelio Hernández-Pando; Romina Rodríguez-Sanoja; Silvia Moreno-Mendieta (PLoS ONE, 2025)
Polysaccharides as immunomodulators are increasingly explored in preclinical studies, showing potential applications for preventing or treating different diseases. Among them is starch, an α-glucan formed by amylose and amylopectin chains. Given their abundance in nature, physicochemical characteristics, and applicability in pharmacy, they are versatile molecules that offer important biotechnological and biomedical advantages. Most studies about starch immunostimulant properties focus on modified-soluble and particulate α-glucans. However, little research has been done on the immunostimulant properties of starch in its natural particulate state. Previously, we have used starch microparticles (SMPs) as carriers for nasal administration of antigens in healthy mice and as a nasal boost and adjuvant of the Bacillus Calmette–Guérin (BCG) vaccine in a murine model of tuberculosis. This study aimed to analyze the effect of SMPs on the activation and polarization profile of murine alveolar macrophages of the MH-S cell line. We evaluated the effect of these SMPs on cell viability, phagocytosis, and expression of surface markers on M0 alveolar macrophages. We also explored the effect of SMPs on nitric oxide production, cytokine secretion, glucose consumption, and lactate release on M0 and previously M1 and M2-polarized alveolar macrophages. The results indicate that these SMPs are phagocytosed without cytotoxic effects for alveolar macrophages and have an immunomodulatory effect on previously polarized M1 macrophages. In M0 and M2 macrophages, the SMPs induced a mixed secretion of cytokines such as TNF-α, IL-10, and IL-12p40, and a significant decrease of TGF-β1. Recognizing the effects triggered by these SMPs on these cells of the innate immune system will allow us to propose rational uses for these SMPs in prophylactic and therapeutic vaccines intended to be used by the nasal/pulmonary route.